2010
DOI: 10.1159/000283033
|View full text |Cite
|
Sign up to set email alerts
|

The T Cell Response to Major Grass Allergens Is Regulated and Includes IL-10 Production in Atopic but Not in Non-Atopic Subjects

Abstract: Background: The incidence of allergic diseases is increasing in industrialized countries and the immunological mechanisms leading to tolerance or allergy are poorly understood. Cytokines with suppressive abilities and CD4+CD25+ regulatory T cells have been suggested to play a central role in allergen-specific responses. The aim was to determine whether major grass allergens induce production of suppressive cytokines in allergic and healthy subjects and to examine the inhibitory effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 80 publications
4
12
0
1
Order By: Relevance
“…When a blocking antibody against the IL-10 receptor was added to the specific allergen-stimulated PBMC cultures, the level of IL-2 increased significantly, and the level of IL-10 showed an increasing trend compared to the cultures that were treated with an isotype antibody control (p = 0.018 and p = 0.237, respectively, Wilcoxon). These data are in agreement with a previously published study [9]. Furthermore, IL-10 can block the production of IL-2 in an indirect manner [51].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…When a blocking antibody against the IL-10 receptor was added to the specific allergen-stimulated PBMC cultures, the level of IL-2 increased significantly, and the level of IL-10 showed an increasing trend compared to the cultures that were treated with an isotype antibody control (p = 0.018 and p = 0.237, respectively, Wilcoxon). These data are in agreement with a previously published study [9]. Furthermore, IL-10 can block the production of IL-2 in an indirect manner [51].…”
Section: Discussionsupporting
confidence: 94%
“…However, in vivo and in vitro induction of Tregs in patients suffering from pollen allergies who have received SIT is a controversial subject. Different in vivo experiments have shown that the frequencies of CD4 + CD25 + CD127 low/- Tregs do not differ between the initiation and maintenance phases of SIT and that, furthermore, similar frequencies of CD4 + CD25 + Tregs can be found in healthy nonatopic controls and atopic patients [9,36]. However, other in vitro experiments have found a significant increase in the frequency of CD4 + CD25 + Foxp3 + /CD127 low Tregs in allergen-stimulated cultures of PBMCs collected prior to and after 24 months of SLIT [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of IL-10-secreting cells and allergy is controversial [26], but PBMCs from grass-allergic patients have an IL-10 response not found in healthy individuals [27]. In vitro, neutralization of IL-10 increased proinflammatory cytokine secretion [28] and allergen-pulsed DCs in the presence of IL-10-induced regulatory cells [29].…”
Section: Discussionmentioning
confidence: 99%